fACTOR STRUCTURE OF PRE-COMPETITIVE TRAINING OF HIGHLY QUALIFIED SPEEDWALKERS - Kolesnikov N.V. ,; Striga S.I. ,; Ponimasov O.E. ,; Fursov V.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to increase the competitive speed of walking at a distance of 20 km by adapting speedwalkers to specific loads in the aerobic, mixed and glycolytic zones. Methods and structure of the study. The factor structure of pre-competitive training of athletes was assessed by examining the parameters of sports activity of 15 masters of sports in race walking for 20 km at the age of 28.5±0.5 years. Based on the results of testing, a training model of functional development was developed, focused on the target indicators of the integral readiness of athletes for competitive starts. Results and conclusions. The factors of special endurance and physical aerobic performance have the greatest correlation with the result of walkers of the master of sports level in the structure of special training. With the growth of qualification, the importance of speed increases and the contribution of special endurance of athletes decreases. This indicates the dynamism of the structure of the special precompetitive training of walkers.